Substitution of Soybean Meal with Fermented Leucaena Leaf Meal (Leucaena leucocephala) in the Diets on the Growth of Tambaqui (Colossoma macropomum) Fingerling - Nadya Oviantari Lubis; Indra Suharman; Adelina Adelina (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2018)
ABSTRACT The research was conducted for 56 days from August to October 2017. The aim of this research was to know percentage of fermented leucaena leaf meal in the diets to substitute soybean meal and its effect on growth and feed efficiency of Tambaqui fingerling. Completely randomized design (CRD) was used in this experiment, with one factor, five level treatments and three replications. The fish used in this research with size 3-5 cm in 0,6-0,8 g of weight. Fish were reared in 1 m3 cages with stocking density 25 fish/cages. Feeding trial were replacing soybean meal with fermented leucaena leaf meal applied to P1 (0%), P2 (10%), P3 (20%), P4 (30%), and P5 (40%)for 35% of protein content. The result showed that fermented leucaena leaf meal gave significant effect (P>0,05) on growth, feed efficiency and feed digestibility of Tambaqui fingerling. Replacement 30% fermented leucaena leaf meal produce the highest specific growth rate 4,9%, feed efficiency 47,1% and feed digestibility 71,26%.Key word :Colossoma macropomum,Fermentation, Growth, Leucaena Leaf Meal, Soybean Meal.